Media cyfrowe a kultura - Piecuch, Aleksander (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
W opracowaniu podjęto próbę zwrócenia uwagi wpływu mediów cyfrowych na kształtowanie się kultury. Jest to temat wielowątkowy i bardzo rozległy, przekraczający możliwości całościowego jego ujęcia w tak krótkim opracowaniu. Stąd zasygnalizowano tylko niektóre aspekty relacji pomiędzy mediami cyfrowymi a kulturą.

The study attempts to draw attention to the influence of digital media on the development of culture. It is a multithreaded and very extensive topic, exceeding the possibilities of its comprehensive approach in such a short study. Thus, only some aspects of the relationship between digital media and culture have been signaled.
Digital media and culture
Keywords: media cyfrowe; kultura; digital media; culture